Strangers No More : Immigration and the Challenges of Integration in North America and Western Europe - Alba, Richard D.; Foner, Nancy, 1945- (Book collections on Project MUSE., 2015)
"Strangers No More is the first book to compare immigrant integration across key Western countries. Focusing on low-status newcomers and their children, it examines how they are making their way in four critical European countries--France, Germany, Great Britain, and the Netherlands--and, across the Atlantic, in the United States and Canada. This systematic, data-rich comparison reveals their progress and the barriers they face in an array of institutions--from labor markets and neighborhoods to educational and political systems--and considers the controversial questions of religion, race, identity, and intermarriage. Richard Alba and Nancy Foner shed new light on questions at the heart of concerns about immigration. They analyze why immigrant religion is a more significant divide in Western Europe than in the United States, where race is a more severe obstacle. They look at why, despite fears in Europe about the rise of immigrant ghettoes, residential segregation is much less of a problem for immigrant minorities there than in the United States. They explore why everywhere, growing economic inequality and the proliferation of precarious, low-wage jobs pose dilemmas for the second generation. They also evaluate perspectives often proposed to explain the success of immigrant integration in certain countries, including nationally specific models, the political economy, and the histories of Canada and the United States as settler societies. Strangers No More delves into issues of pivotal importance for the present and future of Western societies, where immigrants and their children form ever-larger shares of the population"--Provided by publisher.